How can anticipatory action inspire gender inclusion? - Schindler, Alexandra; Mapedza, Everisto D. (International Water Management Institute, 2024)
This year, the United Nation’s theme for International Women’s Day is ‘Invest in women: Accelerate progress; a theme that aims to expose barriers to gender equality and explore gender-responsive opportunities to secure a better future for all. Research shows that in a disaster, women are 14 times more likely to die than men, often because they have less access to extreme weather-related information and fewer resources to respond appropriately to disasters. In 2022, the UN Secretary-General, António Guterres, declared the need for “Early warnings for all.” This declaration highlights the need to tackle disaster-related loss and damage to ensure that everyone on Earth is protected from hazardous weather, water, or climate events. As we seek to safeguard global communities it is imperative that anticipatory action (AA) strategies are designed and implemented to ensure early warnings and long-term adaptation solutions for all genders. Given the elevated risk that women face in times of disaster, mainstreaming gender as an element of anticipatory action is vital.